Consumer Behavior in Banking Products Buying Decision: A Phenomenological Approach of Millennial in Jakarta - Iwan Sukoco; Anita Maulina; H. Bambang Hermanto; Nenden Kostini (Technium Social Sciences Journal, 2020)
This study aims at answering questions about what factors encourage millennials to make decisions in buying banking products and how the efforts are made by banks to attract customers from millennials. In this study, the phenomenological approach of the qualitative research design was employed. Data collection was carried out by semi-structured interviews to dig deeper into the experiences of informants consisting of millennials. Interviews were also conducted with marketing managers from a national private bank to obtain data related to the efforts made by the bank to attract millennial customers. This research shows that the factors that encourage millennials to make decisions in buying banking products are cultural factors (social class), social factors (status) and personal factors (age, occupation and lifestyle) and to attract millennial customers, several private national banks have been trying to launch banking products that suit the lifestyle and needs of millennials with all the conveniences and digital facilities.